The feasibility of implementing the National Strategy for Higher Education and Scientific Research 2024-2034 ( Misurata University as a model ). (Sebha University Conference Proceedings, 2025)
This research aims to assess the feasibility of implementing the National Strategy Project for Higher Education and Scientific Research 2024-2034, using Misrata University as a case study.A questionnaire was used as the research tool, and the descriptive method was adopted due to its suitability for the study's objectives. The research population consisted of faculty members at Misrata University, with a sample of 112 faculty members selected randomly. The research findings are as follows: Given that the National Strategy Project for Higher Education and Scientific Research is intended to commence from early 2024 to late 2034, and this study obtained its results in early 2025 (the second year of the project), the availability of the strategy's provisions is still at a low level. This indicates a failure in the first year and a lack of implementation. Furthermore, the results clearly show the impossibility of applying the National Strategy Project for Higher Education and Scientific Research in its current state. The strategy project has faced numerous challenges and obstacles, including the lack of development in regulations and legislation, insufficient integration of technology in the education and scientific research sector, and issues related to financial support for innovation and scientific research.